TRANSPORT OF PHENOL THROUGH INCLUSION POLYMER MEMBRANE (PIM) USING COPOLY(EUGENOL-DVB) AS MEMBRANE CARRIERS - Agung Abadi Kiswandono; Dwi Siswanta; Nurul Hidayat Aprilita; Sri Juari Santosa (Universitas Gadjah Mada, 2012)
Copoly(eugenol-DVB) with DVB composition of 2%, 6% and 12% had been prepared and characterized by FTIR spectroscopy. The copolymers were used as membrane carriers for the transport of phenol using the polymer inclusion membranes (PIM) based on polyvinylchloride (PVC) as membrane support. The experimental conditions for investigation of the transport of phenol through the membranes were pH of the source phase, NaOH concentration in the stripping phase, membrane thickness, phenol concentration and transport time. The results showed that the optimum condition for phenol transport was achieved on the membrane based on copoly(eugenol-DVB) 12% with the transport efficiency of 75.6% at pH of the source phase of 4.5, NaOH concentration of 0.25 M and transport time of 48 h. The reaction follows first order kinetics with mass transfer coefficient (k) of 1.02×10-5 m/s and permeability (Ps) of 8.5×10-6 m/s.